Fake News on Social Media A Threat to Social Conditions: Critical Discourse Study - Kholid, Kholid; Zulpahmi, Zulpahmi; Zainul, Zainul (Universitas PGRI Semarang, 2023)
The phenomenon of using language in cyberspace or social media is trending with various up-to-date applications with the aim of being more effective and efficient communicating. This research really needs to be done because there is rampant communication that is not wise through social media, in addition, no one has studied this phenomenon from a language perspective. This research focuses on fake news texts in the media social context with a focus on discourse, namely the impact of fake news texts on social conditions. The purpose of this study is to describe in depth the problem of the threat of spreading fake news texts on social media to social conditions. The aim is to find out and analyze threats in the form of the impact of spreading fake news on social media on social conditions. Methods and techniques of data collection by way of observation, documentation of the instrument with a questionnaire. Based on the results of an analysis of the data found related to the spread of fake news texts on social media, it has an impact on social conditions in terms of aspects; (a) Aspects of media literacy, less wise in using social media; (b) The economic aspect, the motivation to live instantly is reflected in unhealthy economic competition; (c) Health aspect, reflected by people with unhealthy lifestyles and obstacles to health stability nationally; (d) Political aspects, the occurrence of dishonest and unfair political implementation in the process of political contestation.